Новый подход к созданию устройств с энергонезависимой памятью на основе Si-МОП-транзисторов - Gulyaev, Yu. V.; Zhdan, A. G.; Chucheva, G. V. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
A new approach to the creation of a long-term random-access memory based on the effect of the electron-ion interaction on Si-MOS-transistors is proposed. The difference in levels of signals «zero» and «unit» depends on the regime of reading, and can vary widely. Time of recording-erasing is determined by the size of the transistor and makes some milliseconds. Obtained results allow to suggest, that compared with the traditional flash memory, such storage device will be more reliable and durable.